International Conference on Transportation and Development 2022. selected papers from the International Conference on Transportation and Development 2022, Seattle, Washington, May 31-June 3, 2022 - Wei, Heng (Civil engineer) (American Society of Civil Engineers, 2022)
The third volume of the proceedings of the International Conference on Transportation and Development 2022, held in Seattle, Washington, May 31-June 3, 2022. This collection contains 26 peer-reviewed papers on transportation safety. Topics include: include: automated warning systems; safety barriers and markers; crash prediction models; speed limits and enforcement; driver fatigue and abilities; and weather and road conditions.